2006
DOI: 10.1016/j.euje.2005.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of strain and strain rate imaging for the assessment of regional left atrial deformation: A study in normal subjects

Abstract: SR/epsilon imaging for the quantification of longitudinal myocardial LA deformation was shown to be feasible and the normal values were reported and validated. These data may improve the understanding of the LA pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
149
1
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(167 citation statements)
references
References 30 publications
9
149
1
8
Order By: Relevance
“…In this manner, STE allows for the assessment of myocardial function independent of cardiac translation and angle of insonation 3, 4, 10. In people, reference range values, feasibility, and reproducibility of STE for the study of LA mechanics have been extensively documented 12, 13, 14, 15. Furthermore, the clinical and prognostic importance of STE variables has been demonstrated in numerous pathophysiologic conditions typically associated with abnormal LA function, including MMVD, atrial fibrillation, systemic hypertension, and dilated, as well as hypertrophic, cardiomyopathy 3, 4, 10, 16, 17.…”
mentioning
confidence: 99%
“…In this manner, STE allows for the assessment of myocardial function independent of cardiac translation and angle of insonation 3, 4, 10. In people, reference range values, feasibility, and reproducibility of STE for the study of LA mechanics have been extensively documented 12, 13, 14, 15. Furthermore, the clinical and prognostic importance of STE variables has been demonstrated in numerous pathophysiologic conditions typically associated with abnormal LA function, including MMVD, atrial fibrillation, systemic hypertension, and dilated, as well as hypertrophic, cardiomyopathy 3, 4, 10, 16, 17.…”
mentioning
confidence: 99%
“…S/SR imaging methods have been used in the assessment of LV function in many cardiovascular diseases (14)(15)(16)(17). S/SR imaging derived from TDI has been validated by quantitative assessment of regional LA deformation in healthy subjects (10,14). In a few studies, LA deformation has been shown to be affected in various etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial mechanical cycle is consisted of three phases: reservoir phase (RP) during LV systole, conduit phase (CP) during early and mid-period of the ventricular diastole, and pump phase (PP) which enhance LV filling during late diastole (9)(10)(11). Although LA volumes assessed by conventional echocardiography provide information about the global function, it remains inadequate for the quantitative assessment of myocardial function separately during each of these phases.…”
Section: Introductionmentioning
confidence: 99%
“…2,28 Immediately after the BMV procedure a repeat echocardiogram was performed to define the success of procedure as mentioned previously. 15,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] All patients, in whom BMV was successful, underwent a repeat echocardiographic evaluation 24-48 hours after the procedure for the measurement of post-procedural parameters.…”
Section: Echocardiographymentioning
confidence: 99%
“…20 The left atrial phasic volumes were calculated by the modified Simpson's method from the apical four chamber view at the onset of P-wave on the ECG [pre-atrial contraction volume, V p ( Figure 1 . [21][22][23] These values were corrected for the body surface area (BSA). For the assessment of LA mechanical functions, the following indices calculated from the volumes were used.…”
Section: Echocardiographymentioning
confidence: 99%